2021
DOI: 10.1002/eat.23601
|View full text |Cite
|
Sign up to set email alerts
|

Clinical moderators and predictors of cognitive‐behavioral therapy by guided‐self‐help versus therapist‐led for binge‐eating disorder: Analysis of aggregated clinical trials

Abstract: Objective: Cognitive-behavioral therapy (CBT)-therapist-led (CBTth) and guidedself-help (CBTgsh)-has efficacy for binge-eating disorder (BED) but many patients do not benefit sufficiently. We examined predictors and moderators for these two CBT methods. Method: Data were aggregated from randomized controlled trials (RCTs) testing psychosocial treatments for BED in the U.S. Predictors and moderators of outcomes (treatment completion and binge-eating remission) were examined in N = 457 participants who received … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 40 publications
2
7
0
Order By: Relevance
“…Likewise, interpersonal deficits are integral to IPT 153 and to a lesser degree in DBT 154 and CBT-E 152 . Regarding moderators and predictors of treatment outcome in BED; there is a need for a specific synthesis in this area and findings have been hard to replicate, however, features associated with a better outcome are an early response to therapy (reduction of binge-eating within the first weeks), an absence of substance use disorder, lower age and BMI, and good premorbid interpersonal functioning 157,162 , and recent data from CBT trials identified low weight concern as a predictor for remission 163 and a history of trauma as negative predictor of treatment success 164 .. Overall, around half of people with BED achieve abstinence from binge-eating, which is maintained at 12-month follow-up; however, longer-term outcomes are less clear 165 .…”
Section: [H2] Psychological Treatmentsmentioning
confidence: 99%
“…Likewise, interpersonal deficits are integral to IPT 153 and to a lesser degree in DBT 154 and CBT-E 152 . Regarding moderators and predictors of treatment outcome in BED; there is a need for a specific synthesis in this area and findings have been hard to replicate, however, features associated with a better outcome are an early response to therapy (reduction of binge-eating within the first weeks), an absence of substance use disorder, lower age and BMI, and good premorbid interpersonal functioning 157,162 , and recent data from CBT trials identified low weight concern as a predictor for remission 163 and a history of trauma as negative predictor of treatment success 164 .. Overall, around half of people with BED achieve abstinence from binge-eating, which is maintained at 12-month follow-up; however, longer-term outcomes are less clear 165 .…”
Section: [H2] Psychological Treatmentsmentioning
confidence: 99%
“…A number of patient variables have been evaluated as predictors, including – but not limited to – various eating-disorder psychopathology scales/measures as well as specific features such as overvaluation of shape/weight, self-control, depression and negative affect, and psychiatric comorbidity (e.g. Anderson et al, 2020; Grilo, Masheb, & Crosby, 2012a; Grilo, Thompson-Brenner, Shingleton, Thompson, & Franko, 2021; Lydecker & Grilo, in press; see online Supplementary Materials). Research has also tested treatment parameters (Thompson-Brenner et al, 2013) and processes such as rapid response to treatment (⩾65% reduction in binge-eating episodes within the first month of treatment; Grilo, White, Masheb, & Gueorguieva, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…We offer, however, some cautionary considerations for non‐responders to initial treatments, for whom guided self‐help CBT might not be the ideal next step (i.e., rather than therapist‐led CBT). A recent re‐analysis of aggregated data from controlled trials evaluating CBT interventions for BED revealed that after statistical adjustment for demographic and clinical characteristics, therapist‐led CBT was associated with significantly better outcomes than guided self‐help methods (Grilo et al, 2021). Relatedly, in a stepped care trial for BED, when patients who did not have a rapid response to initial treatment with BWL were switched to guided self‐help CBT, little additional benefit was observed (Grilo et al, 2020).…”
Section: Discussionmentioning
confidence: 99%